DNA Radiosensitization: The Search for Repair Refractive Lesions Including Double Strand Breaks and Interstrand Crosslinks - Gantchev, Tsvetan G.; Dextraze, Marie-Eve; Hunting, Darel J. (IntechOpen, 2011)
None